2020
DOI: 10.1055/s-0040-1715801
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal Dislocation of the Trapezoid with Metacarpal Instability: A Boxing Injury

Abstract: Background The second and third metacarpals are firmly attached, immobile structures which for the stable pillar of the hand. The trapezoid has been described as the keystone of the wrist, allowing a wide range of functional motion as well as inherent anatomic and biomechanical stability to the carpus. Case Description We describe a novel boxing injury with a 180-degree in situ dislocation of the right trapezoid with concomitant second and third carpometacarpal (CMC) joint dislocations. Open anatomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…Noted that CMCJ dislocations can be associated with concomitant MCPJ (fracture-)dislocation injury as well [24,25]. Moreover, Gaheer and Ferdinand [26] reported about one case with a third metacarpal base fracture associated with primarily missed dislocations of the CMCJ IV and V, Brinkman et al [27] observed one case with CMCJ II-V dislocations associated with a concurrent fracture of the hamate bone, and Feder et al [28] reported about one case with a 180° in situ dislocation of the trapezoid bone associated with concomitant CMCJ II and III dislocations. Noted was well that a newest study including 139,931 polytraumatized patients revealed that the relative portion of primarily missed hand injuries is 6.6% (excluding distal radius fractures), and 11.2% of these patients sustained carpal fractures/ dislocations [29].…”
Section: Discussionmentioning
confidence: 99%
“…Noted that CMCJ dislocations can be associated with concomitant MCPJ (fracture-)dislocation injury as well [24,25]. Moreover, Gaheer and Ferdinand [26] reported about one case with a third metacarpal base fracture associated with primarily missed dislocations of the CMCJ IV and V, Brinkman et al [27] observed one case with CMCJ II-V dislocations associated with a concurrent fracture of the hamate bone, and Feder et al [28] reported about one case with a 180° in situ dislocation of the trapezoid bone associated with concomitant CMCJ II and III dislocations. Noted was well that a newest study including 139,931 polytraumatized patients revealed that the relative portion of primarily missed hand injuries is 6.6% (excluding distal radius fractures), and 11.2% of these patients sustained carpal fractures/ dislocations [29].…”
Section: Discussionmentioning
confidence: 99%